2008
DOI: 10.1007/s12206-008-0748-3
|View full text |Cite
|
Sign up to set email alerts
|

Steam explosion experiments using partially oxidized corium

Abstract: Two steam explosion experiments were performed in the TROI (Test for Real cOrium Interaction with water) facility by using partially oxidized molten corium (core material), which is produced during a postulated core melt accident in a nuclear reactor. A triggered steam explosion occurred in one case, but none occurred in the other case. The dynamic pressure and the dynamic load measured in the former experiment show a stronger explosion than those performed previously with oxidic corium. Meanwhile, a steam exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…It has been reported that serious steam explosion may take place when liquid water contacts liquid metal or salt (Nelson et al, 2005;Kim et al, 2008). This paper speculates on this issue because the pipeline may be constructed over a long distance and the leak of soil or channel water into the pipeline due to seismic or corrosive causes may occur.…”
Section: Intermediate Working Fluidsmentioning
confidence: 78%
See 2 more Smart Citations
“…It has been reported that serious steam explosion may take place when liquid water contacts liquid metal or salt (Nelson et al, 2005;Kim et al, 2008). This paper speculates on this issue because the pipeline may be constructed over a long distance and the leak of soil or channel water into the pipeline due to seismic or corrosive causes may occur.…”
Section: Intermediate Working Fluidsmentioning
confidence: 78%
“…In comparison, the corrosion attack on the pipes by steam, supercritical water, and supercritical CO 2 depend on temperature and pipe materials. As to the molten salts, the research has been performed in the past decades on the chemical corrosion and abrasion phenomena (Peterson et al, 2003;Sabharwall et al, 2010), there are still many unknowns today and the molten salt chemistry plays a major role in the viability demonstration of molten salt nuclear reactor (Nelson et al, 2005;Kim et al, 2008). So it is concluded that the intermediate heat exchanger may have the same viability challenge if using molten salt as the secondary heat transfer fluid.…”
Section: Intermediate Working Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) 한국원자력연구원 에서는 이러한 실제 원자로 물질에 대한 문제를 해결하기 위하여 원자로 물질의 다양한 조성을 사 용한 TROI 실험을 수행하고 있다. (5) 실험적인 연구가 스케일링 문제 등에 있어서 원 자로에 직접 적용하기는 어렵기 때문에 해석적인 연구도 수행되었다. TEXAS-V 코드 (6) 를 포함한 여 러 증기폭발 해석코드가 실험적인 관찰을 근거로 하여 개발되었다.…”
Section: 서 론unclassified
“…Nevertheless, further research regarding machine learning is still warranted, mainly due to different distribution of data sets required in drug discovery when compared to traditional artificial intelligence input data. The interested reader is referred to comprehensive reviews [34–39], in which the authors discuss advances in the field of drug discovery based on various artificial intelligence approaches.…”
Section: Introductionmentioning
confidence: 99%